The global burden of paediatric and neonatal sepsis: a systematic review. Issue 3 (March 2018) - Fleischmann-Struzek, Carolin; Goldfarb, David M; Schlattmann, Peter; Schlapbach, Luregn J; Reinhart, Konrad; Kissoon, Niranjan
Summary: The incidence of sepsis is highest in neonates and children, yet the global burden of sepsis in these age groups has not been assessed. We reviewed available evidence from observational epidemiological studies to estimate the global burden and mortality of sepsis in neonates and children. We did a systematic review and meta-analysis of studies reporting population-based sepsis incidence in neonates and children, published between 1979 and 2016. Our search yielded 1270 studies, 23 of which met the inclusion criteria; 16 were from high-income countries and seven from middle-income countries. 15 studies from 12 countries reported complete data and were included in the meta-analysis. We found an aggregate estimate of 48 (95% CI 27–86) sepsis cases and 22 (14–33) severe sepsis cases in children per 100 000 person-years. Mortality ranged from 1% to 5% for sepsis and 9% to 20% for severe sepsis. The population-level estimate for neonatal sepsis was 2202 (95% CI 1099–4360) per 100 000 livebirths, with mortality between 11% and 19%. Extrapolating these figures on a global scale, we estimate an incidence of 3·0 million cases of sepsis in neonates and 1·2 million cases in children. Although these results confirm that sepsis is a common and frequently fatal condition affecting neonates and children globally, few population-based data are available from low-income settings and the lack of standardisation of diagnostic criteria and definition of sepsis in the reviewed studies are obstacles to the accurate estimation of global burden. Robust epidemiological monitoring to define global sepsis incidence and mortality in children is urgently needed.